2018
DOI: 10.1002/cptc.201700200
|View full text |Cite
|
Sign up to set email alerts
|

Facile Templateless Fabrication of a Cobalt Oxyhydroxide Nanosheet Film with Nanoscale Porosity as an Efficient Electrocatalyst for Water Oxidation

Abstract: The development of efficient catalysts for water oxidation is widely required because the efficiency of fuel production by artificial photosynthesis is severely limited by the sluggish kinetics of water oxidation. A unique CoO(OH) nanosheet (CoO (OH)-NS) film having porosity in nanoscale dimensions has been synthesized by a facile electrochemical technique without the assistance of any template. The SEM image exhibited that the film is composed of nanosheets that are well scattered and formed uniformly by unid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…Conventionally, OER anodes have been prepared by various physical and chemical techniques, including hydrothermal, 36 electrodeposition, 39,40 electrophoresis, 41−43 spin coating, 44,45 drop-casting, 46 self-assembly, 47 dip coating, 48 screen printing, 49 chemical bath deposition, 50 photochemical formation, 51 and pulsed laser deposition. 19 However, facile and energyconserving preparation techniques of the OER anodes are absolutely needed in view of their extensive availability in a nod to current preparation methods of OER anodes using various physical and chemical techniques.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventionally, OER anodes have been prepared by various physical and chemical techniques, including hydrothermal, 36 electrodeposition, 39,40 electrophoresis, 41−43 spin coating, 44,45 drop-casting, 46 self-assembly, 47 dip coating, 48 screen printing, 49 chemical bath deposition, 50 photochemical formation, 51 and pulsed laser deposition. 19 However, facile and energyconserving preparation techniques of the OER anodes are absolutely needed in view of their extensive availability in a nod to current preparation methods of OER anodes using various physical and chemical techniques.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Conventionally, OER anodes have been prepared by various physical and chemical techniques, including hydrothermal, electrodeposition, , electrophoresis, spin coating, , drop-casting, self-assembly, dip coating, screen printing, chemical bath deposition, photochemical formation, and pulsed laser deposition . However, facile and energy-conserving preparation techniques of the OER anodes are absolutely needed in view of their extensive availability in a nod to current preparation methods of OER anodes using various physical and chemical techniques. ,, Herein, we have amazingly found that loading-controllable single- and mixed-metal oxide films adhered rigidly on various electrode substrates are easily prepared from precursor solutions or suspensions containing corresponding metal salts in methanol/1-methyl imidazole (MeIm) mixed solvents. Material hunting for superior OER anodes has been performed by preparing a variety of single- and mixed-metal oxide films using this method.…”
Section: Introductionmentioning
confidence: 99%